The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.3390/ma16103783
|View full text |Cite
|
Sign up to set email alerts
|

Recent Progress of Cement-Based Materials Modified by Graphene and Its Derivatives

Abstract: Graphene, with its excellent properties and unique structure, has been extensively studied in the context of modifiable cement-based materials. However, a systematic summary of the status of numerous experimental results and applications is lacking. Therefore, this paper reviews the graphene materials that improve the properties of cement-based materials, including workability, mechanical properties, and durability. The influence of graphene material properties, mass ratio, and curing time on the mechanical pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 86 publications
(114 reference statements)
0
0
0
Order By: Relevance
“…The more desirable properties of Graphene for construction applications are the mechanical, thermal, and durability properties that have stirred up more research. The ability of Graphene to bond with the cementitious product has shown great promise for its utilisation in the construction industry (Li et al, 2023).…”
Section: Mechanical Physical and Thermal Properties Of Graphenementioning
confidence: 99%
See 4 more Smart Citations
“…The more desirable properties of Graphene for construction applications are the mechanical, thermal, and durability properties that have stirred up more research. The ability of Graphene to bond with the cementitious product has shown great promise for its utilisation in the construction industry (Li et al, 2023).…”
Section: Mechanical Physical and Thermal Properties Of Graphenementioning
confidence: 99%
“…Graphene and its derivatives have been applied in nanotechnology, biomedical, bioelectrical, and energy sectors (Geim and Novoselov, 2007), (Schwierz, 2010), (Li et al, 2019) and (Choi et al, 2013). Recent studies have shown great promise for Graphene application construction (Li et al, 2023). Graphene was successfully used to reinforce asphalt roads to increase strength and durability, reducing the maintenance cost of these roads (Jyothirmai, Kiranmai and Vagdevi, 2020).…”
Section: Application Of Graphene As a Construction Materialsmentioning
confidence: 99%
See 3 more Smart Citations